Menggagas Judicial Activism dalam Putusan Presidential Threshold di Mahkamah Konstitusi - Bagus Surya Prabowo (Jurnal Konstitusi, 2022)
This study aims to explain the application of judicial activism carried out by the Constitutional Court and the reasons for the need for the Constitutional Court to apply judicial activism in the presidential threshold decision through normative juridical research by explaining interrelated principles. The study results show that the Constitutional Court often uses judicial activism as in the Decisions of the Constitutional Court Number 5/PUU-V/2007 and Number 102/PUU-VII/2009. Based on the two decisions, there are at least three considerations of the Constitutional Court in implementing judicial activism that has been fulfilled in cases of presidential threshold, namely, 1) political discrimination, 2) violations of constitutional rights, and 3) a socio-political emergency occurs. Therefore, the Constitutional Court has a basis for testing the threshold that violates morality, rationality, and intolerable injustice. Thus, the Constitutional Court should use judicial activism to give appreciation for substantial justice to revive the value of expediency and justice in society.